A Study on Islamic Culture during the Mughal Era in India - Fery Darmawan; Haidar Putra Daulay; Solihah Titin Sumanti (The Future of Education Journal, 2024)
The aim of this study is to analyze the history of the formation and development of the Mughal Dynasty. This research will also explore the advancements in civilization and the intellectual thought during this period, as well as identify the factors that led to its decline during the reign of the dynasty. In the classical and medieval eras, Islamic civilization was recognized as one of the most brilliant civilizations. During this time, no other civilization could rival its greatness. The influence of Islam spread to various regions, including India. In India, the Islamic influence was significant, as evidenced by the rise of several Islamic dynasties such as the Mamluk Dynasty (1206-1290), the Khalji Dynasty (1290-1320), the Tughluq Dynasty (1320-1413), and others. Among all these dynasties, the Mughal Dynasty stands out as the most prominent. This dynasty was the Islamic power that ruled India from the 16th century to the 19th century, and it was one of the three major dynasties (Mughal, Ottoman, and Safavid) that had a significant impact on the Islamic world during the medieval period. The Mughal Dynasty played a crucial role in the advancement of Islam in India, encompassing political, economic, artistic, cultural, religious, and scientific aspects.